2014
DOI: 10.1038/onc.2014.411
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant IDH3α expression promotes malignant tumor growth by inducing HIF-1-mediated metabolic reprogramming and angiogenesis

Abstract: Cancer cells gain a growth advantage through the so-called Warburg effect by shifting glucose metabolism from oxidative phosphorylation to aerobic glycolysis. Hypoxia-inducible factor 1 (HIF-1) has been suggested to function in metabolic reprogramming; however, the underlying mechanism has not been fully elucidated. We found that the aberrant expression of wild-type isocitrate dehydrogenase 3α (IDH3α), a subunit of the IDH3 heterotetramer, decreased α-ketoglutarate levels and increased the stability and transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 31 publications
4
116
0
1
Order By: Relevance
“…Identification of a critical regulatory step for the PER 2‐mediated activation of HIF ‐1. (A) After being transiently cotransfected with the HIF ‐1α promoter‐luc reporter gene ( pHIF ‐1α promoter‐luc plasmid ), pRL / TK as an internal control, and either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to the dual luciferase assay and western blotting using the indicated antibodies. (B) After being transiently transfected with either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to qRT ‐ PCR to quantitate the mRNA levels of HIF ‐1α and western blotting using the indicated antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of a critical regulatory step for the PER 2‐mediated activation of HIF ‐1. (A) After being transiently cotransfected with the HIF ‐1α promoter‐luc reporter gene ( pHIF ‐1α promoter‐luc plasmid ), pRL / TK as an internal control, and either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to the dual luciferase assay and western blotting using the indicated antibodies. (B) After being transiently transfected with either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to qRT ‐ PCR to quantitate the mRNA levels of HIF ‐1α and western blotting using the indicated antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…(B) After being transiently transfected with either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to qRT ‐ PCR to quantitate the mRNA levels of HIF ‐1α and western blotting using the indicated antibodies. (C) After being transiently cotransfected with the HIF ‐1α‐5′ UTR ‐luc reporter gene ( pGL 3/ HIF ‐1α5ʹ UTR ‐luc plasmid ), pRL / TK as an internal control, and either pc DNA 4/ PER 2‐ myc ‐His ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and subjected to the dual luciferase assay and western blotting using the indicated antibodies. (D) After being transiently cotransfected with the SV 40p‐ HIF ‐1α ODD (548–603 a.a.)‐luc reporter gene ( pGL 3/ ODD ‐Luc plasmid (39)), pRL / TK as an internal control, and either pc DNA 4/ PER 2 ( PER 2) or pc DNA 4/ myc ‐His A ( EV ), HeLa cells were cultured under normoxic or hypoxic conditions, and then subjected to the dual luciferase assay and western blotting using the indicated antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…One prominent example is in the field of cancer research. The mRNA expression levels of IDH3α and VEGF-A were used and visualized as main indicators in 10 major groups of normal tissues 21 in conjunction with the calculated prognostic values by the PrognoScan database 22 . Another example is a study of murine colon proteomes in which colon-specific genes in the mouse version of RefEx were compared to a list of genes from murine colon proteomes that was generated by the researchers’ own results 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was a synergistic interaction effect of the three treatments on decreasing MVD in Hep-2 and Tu212 xenografts. Some studies have shown that downregulation of HIF-1α alone decreased intratumoral MVD [37, 38]. However, others have found that HIF-1α and GLUT-1 were not correlated with MVD in patients with locally advanced cervical cancer [39].…”
Section: Discussionmentioning
confidence: 99%